Do Business Angels' Investments Make It Easier to Raise Follow‐on Venture Capital Financing? An Analysis of the Relevance of Business Angels' Investment Practices. (3rd June 2021) - Capizzi, Vincenzo; Croce, Annalisa; Tenca, Francesca
Abstract: In this paper, we shed light on interactions among the various investors operating within the entrepreneurial finance ecosystem. Specifically, we aim to investigate what business angel (BA) investment practices are correlated with follow‐on venture capital (VC) financing, and uncover the strategies that determine a complementary‐based or a substitution‐based relationship with VCs. We analysed a sample of 176 companies that received a BA investment during 2008–2016 and collected financial data over a 10‐year period after the BA investment. The data examined indicate that BAs' selectivity, as measured by their rejection rate, and BAs' affiliation to an angel network, are positively related with the probability of raising follow‐on VC financing. However, a high level of BAs' monitoring activity negatively influences the probability of obtaining VC funding. Interestingly, BA networks do affect this relationship. The positive impact of BAs' rejection rate is informative for VC decisions if the BA does not invest through a network. Conversely, a high level of monitoring may convey a negative signal for VC, particularly if the BA is affiliated to a network. These results extend our knowledge of the investment practices of BAs and their role in allowing angel‐backed companies to raise follow‐on VC financing.